Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.3 - Polynomial Functions, Graphs, and Composition - 4.3 Exercises: 65

Answer

9

Work Step by Step

We are asked to find $(g∘f)(3)$. We know that $(g∘f)(x)=g(f(x))$. Therefore, $(g∘f)(3)=g(f(3))$. From the first table, we see that $f(3)=1$. From the second table, we see that $g(1)=9$. Therefore, $g(f(3))=g(1)=9$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.